PENGEMBANGAN MODEL PEMBELAJARAN BAHASA ARAB BERBASIS TEORI MULTIPLE INTELLIGENCE (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2015)
The discovery of the theory of Multiple Intelligence by Howard Gagnerhas changed the paradigm of education and learning. If the old paradigm view that intelligence is a single learner who is only measured by IQtests, then the paradigm of Multiple Intelligence view that intelligenceis plural learners. Each individual has the advantage of certainintelligence that may be different with advantages that others have. That fact has implications for the importance of changing patterns ofeducation and learning, including learning Arabic, from the pattern that is only oriented to the development of intellectual intelligence (IQ) to the pattern of intelligence that takes into account the diversity oflearners.This paper describe show the development of Arabic languageinstruction model based on the theory of Multiple Intelligence. Themodel in question is a model of the development of Arabic languagelearning component which includes the development of Arabic languagelearning goals, teachers’ roles, attitudes and treatment of students, andthe development of materials, methods, media, and evaluating the resultsof learning Arabic, all of which were based on intelligence insight plural(Multiple Intelligence).